2006
DOI: 10.1379/csc-208.1
|View full text |Cite
|
Sign up to set email alerts
|

The stress protein gp96 is not an activator of resting rat bone marrow–derived dendritic cells, but is a costimulator and activator of CD3+ T cells

Abstract: Although low doses of tumor-derived stress protein gp96 elicit protective immunity to the tumor from which it is isolated, protection is lost at high doses because of the induction of immunoregulatory CD4 ϩ T cells. This study evaluated the influence of gp96 on resting rat bone marrow-derived dendritic cells (BMDCs) and purified CD3 ϩ T cells. In contrast to previous reports, gp96 had no effect on adhesion and costimulatory molecule expression by BMDCs, nor did it influence interleukin (IL)-10 and IL-12 secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 67 publications
(76 reference statements)
0
17
0
Order By: Relevance
“…Mechanisms of action have been partially elucidated to include interaction with APC, posttranslational folding of TLR, Ag cross-presentation and activation of CTL. However, its effectiveness in immunotherapy seems to be limited in mice models [4] and in clinical trials [11,23,24]. The factors that determine the outcome of an effective immune response are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms of action have been partially elucidated to include interaction with APC, posttranslational folding of TLR, Ag cross-presentation and activation of CTL. However, its effectiveness in immunotherapy seems to be limited in mice models [4] and in clinical trials [11,23,24]. The factors that determine the outcome of an effective immune response are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…T cells [4], increasing cell proliferation and secretion of cytokines. The gp96 protein also induces innate immune responses.…”
mentioning
confidence: 99%
“…Although this sequence of events is commonly accepted, we have been unable to demonstrate that gp96 influences the phenotype, function, or activation status of rat bone marrow-derived DCs (Mirza et al, in press). We have also shown that it does not bind to these cells in a receptor-mediated manner; rather, it is internalized by pinocytosis (Mirza et al 2006).…”
Section: Discussionmentioning
confidence: 80%
“…DCs can subsequently present antigenic peptides that are derived from pinocytosed exogenous material to T cells (reviewed in Norbury [2006]). Given that gp96 does not activate DCs (Mirza et al 2006), then the presentation of gp96-associated peptides to responding T cells by APCs that have endocytosed gp96 would occur in the absence of essential costimulatory signals-the consequence of which could be the induction of T-cell populations with the capacity to attenuate inflammatory disease. It is also possible that gp96 directly influences T-cell populations, and in this regard, we (Mirza et al 2006) and others (Banerjee et al 2002) have demonstrated that gp96 can bind to T cells and act as a costimulatory molecule that promotes the secretion of anti-inflammatory type 2 cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Third, in vitro-cultured dendritic cells have been shown to adopt a tolerizing phenotype, rather than a mature or activated phenotype, in the presence of HSPs 10,11 . Fourth, in experimental models of autoimmunity and of tissue or tumour transplants, immunization with HSPs was shown to lead to the induction of regulatory T cells, which suppressed disease or transplant rejection [12][13][14][15][16][17][18][19] .…”
mentioning
confidence: 99%